Situation and solutions to implement social security policies in Nga Son district, Thanh Hoa province, Vietnam - Nguyen, Duyen Thi; Dao, Thuy Thanh (International Journal of Humanities and Education Development (IJHED), 2023)
Analyze the current situation and propose solutions in the implementation of social security policies in Nga Son district, Thanh Hoa province, Vietnam. 155 family support representatives who are enjoying social security policies in 3 sample units: Nga Thuy, Nga Thang and Nga Son town, the sample is taken based on general consultation and guidance of functional departments related to social security policy implementation in Nga Son district , Thanh Hoa province. Statistics and description of the actual situation of implementing social welfare policy in Nga Son district, Thanh Hoa province in terms of: job creation policy, income; social insurance policies, preferential policies and social allowances, basic social service policies. From there, propose solutions to improve the efficiency of organization and implementation of social security policies in Nga Son district, Thanh Hoa province. Conclusion: The study has successfully analyzed the actual situation of implementing social security policies in Nga Son district, Thanh Hoa province in the period of 2020-2022, specifically in the following contents: Employment, income, employment policy, social insurance, social incentives and allowances, basic social services. The policy implementation process still has a number of limitations, such as: The planning policies to organize the implementation still do not have the participation of the people in the implementation process, mainly from the top down. , there has not been much participation of policy beneficiaries. From those limitations, study the orientation of implementing social security policies in Nga Son district and propose 4 groups of possible solutions.